Crystal engineering of 2-periodic Ni- and Co-based, isoreticular, mixed ligand metal-organic frameworks for sorption studies - Baloyi, Nonhlanhla (Department of Chemistry, 2024)
The study of porous materials has been the subject of vast research, with Metal-Organic Frameworks (MOFs) being the front-runner. A MOF is composed of metal ions and organic ligands, and the type of ligand can affect or control pore size, shape, geometry, inner surface, and structural rearrangement of the materials. This allows for tailoring of the structure/properties, and this one of the most appealing features of MOFs and can be of benefit in many applications, for example, enhancing gas sorption capacities. MOFs consisting of mixed ligands, i.e., more than one type of ligand, open the possibility of varying pore directional features in three dimensions independently, thus allowing for further tailoring of properties. This thesis reports the synthesis of novel two-periodic, isoreticular, Ni and Co isoreticular MOFs, of the formulae [Ni(2-nta)(bpe)(H2O)2]n·2(DMA)n (1), [Ni(2-bta)(bpe)(H2O)2]n·2(DMF)n (2), [Co(2-nta)(bpe)(H2O)2]n·2(DMA)n (3) and [Co(2-ata)(bpe)(H2O)2]n·3(DMA)n·(H2O)n (4). These were synthesized from 1,2-bis(4-pyridyl) ethane and terephthalate ligands (2-nitroterephthalic acid, 2-bromoterephthalic acid, 2-aminoterephthalic acid) with functionalities of varying sizes and polarizabilities (-NO2, -Br, -NH2). The possible effects of the functionalities (-Br, -NO2 and -NH2) of the terephthalate ligands on the stability, porosity and sorption properties of the MOFs were investigated. It was found that MOFs 1 − 4 are all isoreticular to each other, although with void spaces ranging from 36 – 52%, with those containing the nitro functionalities, displaying the smaller void spaces. Although, 2 and 4 display higher void spaces than 1 and 3, 1ʹ and 3ʹ show higher sorption, especially in the case of carbon dioxide sorption and water sorption, which were accompanied by hysteresis upon desorption, with 1ʹ showing superior water sorption with a favourable “S-shaped” isotherm. The differences in sorption could not be fully attributed to the group functionalities in terms of their polarities, however the relative degrees of crystallinity of the MOFs (before and after activation) seemed to be the major factor in explaining the large degree of variation in their sorption properties.